“on air”: participation in an online radio show to foster speaking confidence. a cooperative learning-based strategies study (2012)
The daily observation of class sessions has enabled me to recognize that students possess a feeling of self-distrust in oral activities. For this reason, I designed a study carried out with a group of twelve eighth graders. This article illustrates an action research project conducted to enhance students’ confidence when speaking on an online radio show. The data were collected by using surveys applied to students, audio and video recordings and a teacher’s journal. The data analysis procedures included a blend of inductive analysis, grounded theory and trend analysis. Results indicated that the research process prompted students’ speaking confidence through the use of technology. The study was also an opportunity to improve the teacher’s performance, and become a facilitator by steering a pedagogical intervention that allowed students to make decisions to overcome their lack of speaking confidence. La observación diaria de las clases de inglés me ha hecho reconocer que los estudiantes manifiestan una sensación de frustración al participar en actividades de producción oral. Por esta razón decidí diseñar un estudio para desarrollar la confianza de los estudiantes en la producción oral, participando en un programa de radio en línea. Dicho estudio de investigación-acción se llevó a cabo con un grupo de doce estudiantes de octavo grado. Los datos fueron recolectados con encuestas aplicadas a los estudiantes, grabaciones en audio y video y diarios de la docente. El análisis de datos se realizó usando una combinación de análisis inductivo, teoría fundamentada y análisis de tendencias. Los resultados indican que el proceso de investigación fue una experiencia positiva que facilitó la confianza al hablar en lengua extranjera usando la tecnología. El estudio fue también una oportunidad para apoyar y mejorar el trabajo del docente, quien asumió el papel de facilitador al diseñar una intervención pedagógica que permitió a los estudiantes tomar decisiones para superar su falta de confianza en actividades orales.